Farm visit B (Karakul Circulations: Colonial Economies and the Un_Making of Disciplinary Knowledges in Germany and Namibia, 2022)
82 JPEGS documenting participant observation on a farm near Berseba
Keywords: Karakul sheep; Herding; Postcolonialism; South Africa; Agriculture; Colonisation; Namibia; Swakara; Karakul Circulations; Colonial Economies; Karakul Farming; Germany; Colonial South-West Africa; German Colonialism; Karakul Sheep Industry